Global financial accounting and reporting principles and analysis - Walton, Peter J. (Thomson, 2006)
Global Financial Accounting and Reporting is a European-focused introductory financial accounting textbook for students encountering the subject for the first time at MBA and Masters level. Structured around European IFRS, the second edition of this text has been fully updated to cover recent changes to reporting standards and provides a concise and accessible guide to international financial reporting, heavily-supported by real-world examples from multinational company accounts.